Feature Story: Cherish Jean-Baptiste is an outstanding young alumna - External Relations, University of Regina (External Relations, University of Regina, 2015)
At only 32 years of age, Cherish Jean-Baptiste is already thriving in the public sector economic realm, and enriching her community in countless ways. Jean-Baptiste (nee Deegan) graduated from First Nations University of Canada in 2006 with a bachelor’s degree in business administration with a focus on marketing. She now works as a business consultant for Crown Investments Corporation (CIC) and is the president of the First Nations and Métis Fund (FNMF) and First Nations Business Development Program (FNBDP). Staff no